2022
DOI: 10.1002/cbdv.202200345
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Alleviates Mice Intestinal Ischemia‐Reperfusion Injury: A Study Based on Transcriptomics Combined with Functional Experiments

Abstract: BackgroundIt has been reported that intestinal ischemia-reperfusion injury (IIRI) is closely related to in ammatory response, apoptosis and oxidative stress. Ellagic acid (EA) has been proved to have antioxidant and antiin ammatory effects, and can inhibit tumor angiogenesis. The purpose of this study was to investigate the protective effects of EA on IIRI in mice. MethodsA mouse model of IIRI was established by clamping the mesenteric artery. Effects and mechanisms of EA on IIRI were investigate by transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…All of these studies required the use of one animal per sampling incident, which highlights the importance of techniques that optimise the use of experimental animals. [20][21][22][23][24][25][26][27][28][29] In our selective clamping IIRI-BK model, we obtained five samples from the same injured intestine, considerably reducing the number of rats and allowing kinetic studies. In addition, SI morphological damage and villus recovery were comparable with several previous results published by our group and others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All of these studies required the use of one animal per sampling incident, which highlights the importance of techniques that optimise the use of experimental animals. [20][21][22][23][24][25][26][27][28][29] In our selective clamping IIRI-BK model, we obtained five samples from the same injured intestine, considerably reducing the number of rats and allowing kinetic studies. In addition, SI morphological damage and villus recovery were comparable with several previous results published by our group and others.…”
Section: Discussionmentioning
confidence: 99%
“…Among experimental studies focused on gastrointestinal diseases found in the literature, IIRI-and 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats appears as a current model used by many authors and research groups around the world. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For this reason, we selected these two relevant pathologies to evaluate the experimental BK procedure in an intestinal injury scenario. IIRI was used for simulating a model of intestinal intussusception, strangulated hernia or intestinal transplantation.…”
Section: Step 2 Bk Model Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…De los estudios experimentales focalizados en patología de intestino delgado la IIR es un modelo de interés en la actualidad. (91)(92)(93)(94)(95)(96)(97)(98)(99)(100) Materiales y métodos: Se emplearon ratas Wistar hembras (peso 221 ± 13 gr). A las mismas se les proporcionó agua y alimento a demanda previo al acto quirúrgico.…”
Section: Bk Para El Estudio De La Iir Intestinalunclassified